Determinan pemanfaatan pelayanan kesehatan oleh peserta Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) (HEALTH CARE: JURNAL KESEHATAN, 2024)
There has been a decrease in the use of health services utilization by BPJS participants as shown by data on the percentage of visits in 2020 by 12.54%. In 2021, it was 16.83% and in 2022 up to October it was 11.46%. Determinants of health service utilization are influenced by exposure to information, knowledge, income, family support and disease complaints. This study aims to determine the determinants of health service utilization by BPJS participants. This was an analytical survey with a cross-sectional approach. The study population involved all BPJS participants in the work area of Ligung Community Health Center for the 2022 period, as many as 29,303 people, with a sample size of 100 people. The samples were selected using Probability Proportional to Size sampling technique (PPS). Data collection instrument used here was a questionnaire, and data were analyzed using the chi square test. The study results showed that there was a relationship between exposure to information (p-value of 0.000